Recovery of Strategic High-Value Fission Products from Spent Nuclear Fuel During Reprocessing - Holdsworth Alistair F.; Eccles Harry; George Kathryn; Sharrad Clint A. (EPJ Web of Conferences)
Nuclear fission has been identified as a key technology for the Net Zero transition, but high costs and concerns of radioactive wastes hinder wider uptake, and fuel cycle inefficiencies hamper the technology’s long-term sustainability. Closing the fuel cycle through spent nuclear fuel (SNF) reprocessing is the primary method of improving sustainability, but high costs and proliferation concerns limit uptake. Current reprocessing technologies recover only the bulk U and Pu in SNF for further energy generation as MOX (mixed oxide) fuel, leaving behind a wide range of untapped, naturally scarce, high-demand, and -value fission product resources. By recovering these resources, such as the platinum group metals (PGMs – Ru, Rh, Pd, Ag), rare earth elements (REEs – Y, La to Dy), and noble gases (He, Kr, Xe), and various other useful isotopes, from SNF during reprocessing operations, the high costs incurred have the potential to be partially or completely offset, in addition to benefits from reducing waste volumes. This paper provides an overview of this concept with exploration of the most promising candidate targets and feeds within reprocessing, and the necessary actions that will be required to see this concept come to fruition in the coming decades.